Identifikasi Clash Detection pada Proyek Gedung Bertingkat Berbasis Building Information Modeling - Era Agita Kabdiyono; Jalaludin Jalaludin; Rifaldi Adi Saputra Rosario Olsen; Rosario Olsen; M Abdul Aziz (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
High-rise building projects are highly complex because they involve the integration of structural, architectural, and mechanical, electrical, and plumbing (MEP) elements. One of the common problems in the planning stage is the occurrence of design clashes between building elements that are not detected early. Such clashes may lead to design discrepancies, rework, material waste, project delays, and potential cost increases during construction. Therefore, the implementation of Building Information Modeling (BIM) through clash detection is important to improve design coordination and minimize construction errors. This study aims to analyze the implementation of BIM-based clash detection in identifying design clashes in a high-rise building project. The research employed a model-based simulation approach through literature review, project data collection, BIM 3D modeling, clash detection, and classification of clashes among building disciplines. The clash detection process was carried out to identify conflicts between structural, architectural, and MEP elements.The results show that the BIM model was able to visualize the building components in detail and support the identification of interdisciplinary clashes. The detected clashes included conflicts between structure and MEP, architecture and MEP, structure and architecture, and wall elements with MEP components.